2007
DOI: 10.1080/00131880701717230
|View full text |Cite
|
Sign up to set email alerts
|

Role model, hero or champion? Children's views concerning role models

Abstract: Original article can be found at: http://www.informaworld.com/smpp/title~content=t713699076 Copyright Informa / Taylor and Francis Group. DOI: 10.1080/0013188070171723

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 6 publications
9
69
1
Order By: Relevance
“…Here, Bricheno and Thornton's (2007) notion of a role model being followed or looked up to does not quite emulate these behaviours. This challenges the notion of males only being the role models; indeed, as Brownhill (2010) posits, both genders could be considered to be role models (9) … as long as they can model both 'natural' masculine and feminine traits (12).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Here, Bricheno and Thornton's (2007) notion of a role model being followed or looked up to does not quite emulate these behaviours. This challenges the notion of males only being the role models; indeed, as Brownhill (2010) posits, both genders could be considered to be role models (9) … as long as they can model both 'natural' masculine and feminine traits (12).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Gauntlett (2002, p. 214-215) While the importance of role models is generally recognized, their defining characteristics and how they influence education and career choices is still unclear. Analysis of scientific literature reveals that research findings vary: some suggest celebrities are most likely while others have found that family members and friends are still most influential (Bricheno & Thornton, 2007). In higher education, the impact of role models on medical students has been explored (Wright, Wong & Newill, 1997).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…While educational settings are undoubtedly significant in the formation of masculinity and act as authority structures in sanctioning specific ways of being male (Connell 1989), the focus on solutions to the problem of 'underachievement', without questioning the nature of the problem itself, means that many of the underlying structures of 'difference' are not addressed (Cobbett and Younger 2012). Some academic commentators have highlighted the significance of the intersections of gender with class and ethnicity in understanding resistance, negotiation and a range of social practices (Frosh et al 2002;Bricheno and Thornton 2007). Further, factors other than gender impact on constructions of subjectivity available to male teachers (Francis 2008).…”
Section: The Complexity Of Boys' Educational 'Underachievement'mentioning
confidence: 99%
“…Within socialisation theory, it is assumed that there are two natural but separate genders based on biological sex (Hicks 2008) and that the child learns to acquire the 'correct' role by imitating their parents. This approach, which emerged in the 1950s and was (someone who is admired, inspirational -imitated and aspired to, but often unrealistically) or a 'champion' (a person who helps and stands up for someone and who is looked up to and respected) (Bricheno and Thornton 2007).…”
Section: Theorising the 'Male Role Model' Discoursementioning
confidence: 99%